Proceedings of the 22nd International Conference on Computational Linguistics - COLING '08 2008
DOI: 10.3115/1599081.1599138
|View full text |Cite
|
Sign up to set email alerts
|

The choice of features for classification of verbs in biomedical texts

Abstract: We conduct large-scale experiments to investigate optimal features for classification of verbs in biomedical texts. We introduce a range of feature sets and associated extraction techniques, and evaluate them thoroughly using a robust method new to the task: cost-based framework for pairwise clustering. Our best results compare favourably with earlier ones. Interestingly, they are obtained with sophisticated feature sets which include lexical and semantic information about selectional preferences of verbs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The best techniques have been applied successfully to domains such as biomedicine [21] and they have produced promising results with demonstrated improvement on application tasks such as argumentative zoning [22] and metaphor identification [23].…”
Section: Introductionmentioning
confidence: 99%
“…The best techniques have been applied successfully to domains such as biomedicine [21] and they have produced promising results with demonstrated improvement on application tasks such as argumentative zoning [22] and metaphor identification [23].…”
Section: Introductionmentioning
confidence: 99%
“…Such grouping can reduce the parameters used for representing verbs individually. While it is time-consuming to manually classify a large number of verbs, previous studies have shown that it is possible to automatically acquire verb classes from both general [3235] and biomedical texts [15, 36, 37]. For example, Li and Brew (2008) classify 1,300 verbs into 48 Levin classes using Bayesian Multinomial Regression for classification [38].…”
Section: Related Workmentioning
confidence: 99%
“…This evaluation is less influenced by structural differences between two clustering solutions and allows to quantify results in terms of precision and recall. We also calculated APP Adjusted Pairwise Precision [17]: this measure quantifies average cluster purity, weighted by the size of the clusters. This provides additional information on the proportion of the relevant clusters.…”
Section: Baseline and Evaluation Measuresmentioning
confidence: 99%